Psychoeducational intervention for people at high risk of developing another melanoma: a pilot randomised controlled trial. Issue 10 (10th October 2017) - Dieng, Mbathio; Kasparian, NA; Mireskandari, Shab; Butow, Phyllis; Costa, Daniel; Morton, Rachael; Mann, Graham; Menzies, Scott; Cust, Anne
Abstract : Introduction: Information and psychological needs have been reported as one of the greatest areas of unmet needs for patients with melanoma. To respond to these needs, we developed the Melanoma Care Intervention, a developed psychoeducational intervention for people at high risk of developing another melanoma comprising of a newly developed melanoma educational booklet and individually tailored telephone support sessions provided by trained psychologists. The purpose of this study was to investigate the acceptability and feasibility of the Melanoma Care Intervention . Methods: Twenty-four adults (14 men, 10 women, mean age: 58 years, SD: 12.2) at high risk of developing a subsequent primary melanoma were recruited and randomly assigned 1:1 to the intervention (a psychoeducational booklet, a Cancer Council booklet on melanoma and up to five telephone-based sessions with a psychologist) or usual care (Cancer Council booklet only). Acceptability, feasibility, fear of cancer recurrence and secondary psychosocial outcomes were assessed at baseline, 1 and 6 months. Results: Satisfaction and perceived benefits were rated highly for all intervention components, particularly the telephone-based psychology sessions (mean satisfaction and benefits: both 9.27 out of 10, SD=2.41). The quality of information and support provided throughout the trial was rated as 'high' by the intervention group, with a mean score of 4.6 out of a possible 5 (SD=0.9) and 4.2 (SD=1.2) for the control group. Conclusions: The intervention was feasible and acceptable for improving psychological adjustment. Timely access to effective, evidence-based, psychological care is a recognised need for people with melanoma. The intervention is designed to directly address this need in a way that is feasible in a clinical setting, acceptable to patients and health professionals. Trial registration number: The trial was registered with the Australian and New Zealand Clinical Trials Registry on 19/03/2013 (Registration Number: ACTRN12613000304730 ).